Adherence to recommendations for fruit and vegetable intake, ethnicity and ischemic heart disease mortality - Sharma, Sangita (Nutr Metab Cardiovasc Dis, 2013)
BACKGROUND AND AIMS: Ischemic heart disease (IHD) accounts for one-third of annual deaths in the U.S. and mortality rates vary by ethnicity. The association between adherence to dietary guidelines for fruit and vegetable intake with IHD mortality among different ethnic groups has not previously been examined. METHODS AND RESULTS: A prospective cohort design was used to examine the incidence of fatal IHD among participants in the Multiethnic Cohort Study. Participants included 164,617 men and women from five ethnic groups: African American, Native Hawaiian, Japanese American, Latino, and Caucasian. Cox proportional hazards models, stratified by ethnicity and sex, were used to examine associations between adherence with recommended dietary guidelines for fruit and vegetable intake and risk for fatal IHD. The results did not provide evidence that the association between adherence with dietary recommendations for fruit or vegetable intake and IHD mortality varies by ethnicity. Pooled data did provide evidence that adhering to the recommendations for vegetables lowered risk among men (RR Z 0.84, 95% CI: 0.74e0.96) and women (RR Z 0.80, 95% CI: 0.69e0.94). No significant effects were observed for fruit intake. CONCLUSIONS: The effect of dietary intake of fruit and vegetables did not vary by ethnicity, providing evidence that recommendations do not need to be individualized for these special populations. The protective effect observed for vegetable intake among both sexes confirms previous findings and supports the evidence base for promoting diet modification in this direction.